Geology, petrography and microstructures of upper part of the Kathmandu nappe along Balaju to Tadi Khola, northwest of Kathmandu, central Nepal (Journal of Nepal Geological Society, 2025)
This study analyzes the modal mineral composition and microstructural characteristics of rocks from the Balaju-Tadi Khola section to add some insightful information regarding the structural analysis of the region. This study investigates the geological distribution and metamorphic characteristics of the Kulikhani Formation (Bhimphedi Group) and the Tistung, Sopyang, and Chandragiri formations (Phulchauki Group) within the Kathmandu Complex. The northern region is composed of micaceous schist, laminated quartzite, and graphitic schist, while the central area is dominated by various types of gneiss, including augen gneiss, banded gneiss, and migmatite. The gneiss zone spans ~10-15 km in width and is associated with biotite-rich and tourmaline-bearing garnets. The study also identifies two main types of pegmatites: one rich in tourmaline and another in biotite. Petrographic analysis of 14 representative rock samples from the study area reveals a diverse range of metamorphic and sedimentary lithologies, highlighting a complex tectonometamorphic history. Graphitic schist and phyllite exhibit well-developed foliation with quartz, mica, and biotite, indicating moderate- to high-grade metamorphism. Quartzites and metasandstones show dynamic and static recrystallization features such as grain boundary migration and bulging, suggesting deformation at elevated temperatures. Gneissic samples display evidence of high-temperature metamorphism with foam-like textures and sutured grain boundaries. Garnet-bearing schists and calcsilicate rocks further confirm medium to high-grade metamorphic conditions. Limestones from the Sopyang Formation show recrystallization textures typical of low- to medium-grade metamorphism. The widespread presence of dynamic recrystallization across rock types suggests intense tectonic activity and prolonged deformation in the study region. The research shows the complex geological and metamorphic processes forming the Kathmandu Complex.